POSSIBILITIES FOR BOOSTING GROUNDWATER RESOURCE EFFICIENCY IN A GREEN ECONOMY - Musayeva Nigora Nuriddinovna (American Journals Publishing, 2025)
Groundwater resources are essential for sustainable development, especially within the framework of a green economy. Efficient utilization and management of these resources can significantly contribute to environmental conservation, economic growth, and social well-being. This study explores innovative strategies for enhancing groundwater efficiency through technological advancements, policy reforms, and eco-friendly practices. The paper also highlights integrated water resource management approaches, including the use of renewable energy for groundwater extraction, water recycling techniques, and smart irrigation systems.
Keywords: Groundwater management, Green economy, Water conservation, Sustainable development, Renewable energy, Smart irrigation, Water recycling.